Community Perspective Towards Higher Education in Nepal: A Study of Needs and Expectations - Giri, Surendra; Luitel, Binod; Thasineku, Om Chandra; Khanal, Dipak (Education and Development, 2021)
This paper reports a study undertaken to address the concern of relevance of higher education in Nepal, with a view to dig out the community needs, aspirations, expectations, and the factors affecting people’s access to higher education - based on the data collected from 385 household heads and members residing in the communities located in the service areas of 14 colleges belonging to five universities of the country; and the communities include 14 ethnicities categorized under 4 ethnic groups and an additional ‘others’ group. An interview schedule was administered for data collection from the households; and the responses were gathered for analysis. Regarding the community needs, it was found that people primarily realize the importance of academic streams of knowledge, followed by the techno-vocational and ethno-indigenous knowledge. For the purpose of educating their children at higher level, however, people have a tendency of lower preference towards the ethno-indigenous knowledge compared to the remaining two streams. While the individual and family-related factors are found as the main obstacles (affecting factors) towards their children’s access to higher education, they tend to have expectations from the community and colleges for support to increase the access in various ways.